Scratch-resistant high-peel-strength bottomless light coating film and preparation method thereof

By adding spherical synthetic silica and homopolypropylene to the BOPP primerless light film, combined with heating and melting and tensile processes, the problems of poor scratch resistance and low paper coating strength of traditional primerless light films are solved. It has achieved high scratch resistance and paper coating strength, meeting market demand and improving production efficiency and cost-effectiveness.

CN119177088APending Publication Date: 2024-12-24ANHUI GUOFENG PLASTIC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411181666.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The traditional BOPP basecoatless light film has poor scratch resistance and low strength of the substrate surface covering, making it difficult to meet market demand.

Method used

Adopt scratch-resistant primer-free light film composed of a baseless adhesive layer, core layer, sub-lower surface layer and functional layer. The functional layer contains spherical synthetic silica, and the core layer and sub-lower surface layer contain homopolypolypropylene and anti-static The masterbatch is prepared by heating melting and stretching processes to improve the scratch resistance and paper covering strength of the film.

Benefits of technology

It significantly improves the scratch resistance and paper coating strength of the film, meets modern market demands, and improves production efficiency and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005012356420000071
    Figure BDA0005012356420000071
  • Figure BDA0005012356420000081
    Figure BDA0005012356420000081
Patent Text Reader

Abstract

The invention discloses a scratch-resistant high-peel-strength prime-coat-free light film, and belongs to the technical field of functional films. The scratch-resistant prime-coat-free light film sequentially comprises a prime-coat-free bonding layer, a core layer, a secondary lower surface layer and a functional layer from top to bottom, the prime coat-free bonding layer is prepared from the following raw materials in percentage by mass: 4 to 6 percent of anti-bonding master batch and 94 to 96 percent of linear polyethylene; the core layer is prepared from the following raw materials in percentage by mass: 99 to 99.9 percent of homo-polypropylene and 0.1 to 1 percent of antistatic master batch; the secondary lower surface layer is prepared from the following raw materials in percentage by mass: 99 to 99.9 percent of homo-polypropylene and 0.1 to 0.8 percent of antistatic master batch; the functional layer comprises the following raw materials in percentage by mass: 5-8% of spherical synthetic silica and 92-95% of homo-polypropylene; the scratch-resistant high-peel-strength prime-coat-free light film has the advantages of high scratch resistance, uniform thickness, high peel strength of a prime-coat-free bonding layer after extrusion coating of EVA (Ethylene Vinyl Acetate), high paper covering strength and the like, and has excellent scratch resistance and film covering strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional films, and in particular to a scratch-resistant, high-peeling-strength, primer-free light film and a preparation method thereof. Background Art

[0002] In recent years, the market has higher and higher requirements for BOPP film for replica packaging. The traditional BOPP unprimed glossy film can no longer meet the market demand due to poor scratch resistance and low substrate surface strength. Therefore, a film with high scratch resistance and high paper strength is needed to meet the market demand. Unprimed glossy film is mainly used in the pre-coating field to protect and decorate printed materials. The product needs to have good scratch resistance and high heat sealing strength, low haze, high transparency, low haze, good thickness uniformity and other characteristics. The scratch-resistant unprimed glossy film base film only needs to be formed once on the double-drawing equipment without secondary coating, and a film with high scratch resistance, high peel strength and high paper strength can be obtained, and it has the advantages of high production efficiency and low cost. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a scratch-resistant, high peel strength, primer-free glossy film and a preparation method thereof, which solves the problems of poor scratch resistance and low covering strength of the current pre-coated film.

[0004] A scratch-resistant primer-free glossy film, comprising, from top to bottom, a primer-free bonding layer, a core layer, a lower surface layer, and a functional layer;

[0005] The primer-free adhesive layer comprises the following raw materials in percentage by mass: 4-6% anti-sticking masterbatch and 94-96% linear polyethylene;

[0006] The core layer comprises the following raw materials in percentage by mass: 99-99.9% homopolypropylene and 0.1-1% antistatic masterbatch;

[0007] The sub-lower surface layer comprises the following raw materials in percentage by mass: homopolymer polypropylene 99-99.9%, antistatic masterbatch 0.1-0.8%;

[0008] The functional layer comprises the following raw materials in percentage by mass: 5-8% of spherical synthetic silica and 92-95% of homopolymerized polypropylene.

[0009] Preferably, the antistatic masterbatch comprises homopolypropylene and an antistatic agent, and the melt index of the antistatic agent is 10.0 to 20.0 g / 10 min.

[0010] Preferably, the antistatic agent includes glyceryl monostearate, ethoxylated amine and derivatives thereof in a compounding ratio of 1:0.8 to 1:2.

[0011] Preferably, the anti-sticking masterbatch comprises 94-96% of linear polyethylene and 4-6% of anti-sticking agent.

[0012] Preferably, the thickness of the functional layer is 0.8-1.2 um, the thickness of the sub-lower surface layer is 0.8-1.0 um, the thickness of the core layer is 8.9-9.7 um, and the thickness of the primer-free adhesive layer is 0.5-0.9 um.

[0013] A method for preparing a scratch-resistant primer-free glossy film comprises the following steps:

[0014] The raw materials of the functional layer, the lower surface layer and the non-priming adhesive layer are respectively added to three auxiliary extruders, and the raw materials of the core layer are added to the main extruder, heated and melted, and then composite co-extruded through the die head, cooled by a cold roller to form a cast sheet, and the cast sheet is longitudinally stretched, preheated, transversely stretched, shaped, and cooled to obtain the product.

[0015] Preferably, the heating and melting temperature of the functional layer and the sub-lower surface layer is 230-245°C, the heating and melting temperature of the core layer is 250-260°C, and the heating and melting temperature of the primer-free adhesive layer is 230-235°C.

[0016] Preferably, the longitudinal stretching has a stretching ratio of 4.3 to 4.6 and a temperature of 90 to 125°C.

[0017] Preferably, the temperature of the transverse stretching is 155-170°C.

[0018] The anti-scratch primer-free glossy film prepared by the above preparation method or the application of the above anti-scratch primer-free glossy film in paper printing production.

[0019] The beneficial effects of the present invention are as follows:

[0020] The traditional BOPP primerless glossy film has poor anti-scratch performance at the functional level, low peeling strength on the substrate surface, and low paper coating strength, which makes it difficult to meet the needs of the modern market. The present invention adds a spherical synthetic silica functional masterbatch with certain smoothness to the functional level of the BOPP primerless glossy film, thereby reducing the friction coefficient of the film surface, obtaining better anti-scratch performance, and providing better protection and decoration for printed products; a high-viscosity linear low-density polyethylene masterbatch is used on the substrate surface, which greatly improves the peeling strength between the film and EVA and the paper coating strength. At the same time, the product does not need to be coated with a primer, and can be hot-pressed with paper after extrusion coating with EVA, and has excellent film coating strength.

[0021] In summary, the scratch-resistant high peel strength non-primer glossy film of the present invention has good scratch resistance and good paper coating strength, and is widely used in the field of pre-coated paper printing. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Comparative Example 1

[0024] A scratch-resistant, high-peel strength, primer-free glossy film, which is composed of a lower surface layer, a sub-lower surface layer, a core layer, and an upper surface layer in sequence;

[0025] The scratch-resistant, high-peel strength, primer-free glossy film has a functional layer of 5% anti-sticking masterbatch and 95% homopolymer polypropylene. The anti-sticking masterbatch is 4um irregular silica and 5% active ingredient. It has certain slippery properties and a melt index of 7.2.0g / 10min under a standard test of 230°C / 2.16KG.

[0026] The secondary surface layer is 99.6% homopolymer polypropylene and 0.5% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a ratio of 1:0.8. The melt index of the antistatic agent under the 230°C / 2.16KG standard test is 24.3g / 10min.

[0027] The core layer is 99.6% homopolymer polypropylene and 0.5% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxyamine, and the compounding ratio is 1:0.8. The melt index of the antistatic agent under the 230℃ / 2.16KG standard test is 24.3g / 10min.

[0028] The masterbatch of the top surface non-priming adhesive layer is 95% ordinary linear low-density polyethylene and 5% anti-adhesive agent. The melting index of the adhesive masterbatch under the standard test of 230℃ / 2.16KG is 2.18g / 10min; the anti-adhesive agent is 5um spherical synthetic silica, 5% effective ingredient, with certain slippery performance, and the melting index under the standard test of 230℃ / 2.16KG is 8.0g / 10min.

[0029] The anti-scratch layer thickness of the lower surface of the scratch-resistant high peel strength non-primer coated glossy film is 1.2um, the thickness of the next lower surface layer is 0.8um, the thickness of the core layer is 9.3um, and the thickness of the upper surface layer is 0.7um.

[0030] Example 1

[0031] A scratch-resistant, high-peel strength, primer-free glossy film, which is composed of a lower surface layer, a sub-lower surface layer, a core layer, and an upper surface layer in sequence;

[0032] The scratch-resistant, high-peel-strength, primer-free glossy film has a functional layer of 5% anti-stick masterbatch and 95% homopolymer polypropylene. The anti-stick masterbatch is 5um spherical synthetic silica and 5% active ingredient. It has certain slippery properties and a melt index of 9.5g / 10min under a standard test of 230°C / 2.16KG.

[0033] The secondary surface layer is 99% homopolymer polypropylene and 1% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a compounding ratio of 1:0.8. The melt index of the antistatic agent under the 230°C / 2.16KG standard test is 24.3g / 10min.

[0034] The core layer is 99% homopolymer polypropylene and 1% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a compounding ratio of 1:0.8. The melt index of the antistatic agent under a standard test of 230°C / 2.16KG is 24.3g / 10min.

[0035] The top layer of primer-free bonding masterbatch is 94% ordinary linear low-density polyethylene and 6% anti-adhesive agent. The melting index of the bonding masterbatch under the 230℃ / 2.16KG standard test is 2.18g / 10min; the anti-adhesive agent is 5um spherical synthetic silica, 5% effective ingredient, with certain slippery performance, and the melting index under the 230℃ / 2.16KG standard test is 8.0g / 10min.

[0036] Scratch-resistant, high peel strength, no-primer coating, the anti-scratch layer thickness is 1.2um, the thickness of the lower surface layer is 0.8um, the thickness of the core layer is 9.3um, and the thickness of the upper surface layer is 0.7um;

[0037] The method for preparing a scratch-resistant, high-peeling-strength, primer-free glossy film comprises the following steps: respectively adding raw materials of a lower surface layer, a sub-lower surface layer and an upper surface layer into four auxiliary extruders, adding raw materials of a core layer into a main extruder, heating and melting them, and then extruding them through a die head composite co-extrusion, cooling them through a quenching roller to form a cast sheet, longitudinally stretching the cast sheet, and then preheating, transversely stretching, shaping, cooling, pulling and winding, and slitting to obtain the film.

[0038] The heating and melting temperature of the lower surface layer and the second lower surface layer is 230-245°C, the heating and melting temperature of the core layer is 250-260°C, and the heating and melting temperature of the upper surface layer is 230-235°C; the longitudinal stretching ratio is 4.3-4.6, and the temperature is 90-125°C; the transverse stretching temperature is 155-170°C.

[0039] Example 2

[0040] A scratch-resistant, high-peel strength, primer-free glossy film, which is composed of a lower surface layer, a sub-lower surface layer, a core layer, and an upper surface layer in sequence;

[0041] The scratch-resistant, high-peel strength, primer-free glossy film has a functional layer of 8% anti-sticking masterbatch and 92% homopolymer polypropylene. The anti-sticking masterbatch is 5um spherical synthetic silica and 5% active ingredients. It has certain slippery properties and a melt index of 9.5g / 10min under a standard test of 230°C / 2.16KG.

[0042] The secondary surface layer is 99.9% homopolymer polypropylene and 0.1% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a ratio of 1:2. The melt index of the antistatic agent under the 230°C / 2.16KG standard test is 24.3g / 10min.

[0043] The core layer is 99.9% homopolymer polypropylene and 0.1% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a ratio of 1:2. The melt index of the antistatic agent under a standard test of 230°C / 2.16KG is 24.3g / 10min.

[0044] The masterbatch of the top surface non-primer adhesive layer is 96% high-adhesive linear low-density polyethylene and 4% anti-adhesive agent. The melting index of the adhesive masterbatch under the 230℃ / 2.16KG standard test is 3.2g / 10min; the anti-adhesive agent is 5um spherical synthetic silica, 5% active ingredient, with certain slippery performance, and the melting index under the 230℃ / 2.16KG standard test is 9.5g / 10min.

[0045] Scratch-resistant, high peel strength, no-primer coating, the anti-scratch layer thickness is 1.2um, the thickness of the lower surface layer is 0.8um, the thickness of the core layer is 9.3um, and the thickness of the upper surface layer is 0.7um;

[0046] The preparation method of the scratch-resistant high peel strength non-primer coating film is the same as that of Example 1.

[0047] Example 3

[0048] A scratch-resistant, high-peel strength, primer-free glossy film, characterized in that it is composed of a lower surface layer, a sub-lower surface layer, a core layer, and an upper surface layer in sequence;

[0049] Scratch-resistant, high peel strength, non-primer coated film, the functional layer is 5% anti-stick masterbatch, 95% homopolymer polypropylene, the anti-stick masterbatch is 5um spherical synthetic silica, 5% active ingredient, with certain slippery performance. The melt index under the 230℃ / 2.16KG standard test is 9.5g / 10min.

[0050] The secondary surface layer is 99% homopolymer polypropylene and 1% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a ratio of 1:2. The melt index of the antistatic agent under the 230°C / 2.16KG standard test is 24.3g / 10min.

[0051] The core layer is 99% homopolymer polypropylene and 1% antistatic masterbatch. The antistatic agent is a compound of glyceryl monostearate and ethoxylated amine in a compounding ratio of 1:0.8. The melt index of the antistatic agent under a standard test of 230°C / 2.16KG is 24.3g / 10min.

[0052] The top surface non-primer adhesive layer is a high-adhesive masterbatch of 94% linear low-density polyethylene and 6% anti-adhesive agent. The melting index of the bonding masterbatch under the 230℃ / 2.16KG standard test is 3.2g / 10min; the anti-adhesive agent is 5um spherical synthetic silica, 5% active ingredient, with certain slippery performance, and the melting index under the 230℃ / 2.16KG standard test is 8.0g / 10min.

[0053] Adjust the film surface thickness, the anti-scratch layer thickness of the anti-scratch layer of the scratch-resistant high peel strength non-primed glossy film is 1.0um, the thickness of the lower surface layer is 0.8um, the thickness of the core layer is 9.4um, and the thickness of the upper surface layer is 0.8um;

[0054] The method for producing the scratch-resistant, high-peel strength, primer-free glossy film is the same as that in Example 1.

[0055] Test example

[0056] The physical properties of the films obtained in Comparative Example 1 and Examples 1-3 were tested, and the test results are shown in Table 1:

[0057] Table 1 Main physical properties of the film

[0058]

[0059]

[0060] According to Table 1, from the experimental data of Comparative Example 1 and Examples 1 / 2 / 3, it can be seen that the friction coefficient of the functional layer (inside) of the ordinary primer-free film is large and the anti-scratch performance is poor. The friction coefficient of the functional layer of Example 1 using a high proportion of high anti-adhesive masterbatch is significantly reduced, and the anti-scratch performance of the film is well improved. The peeling strength and paper covering strength of Comparative Example 1 are both low, and the peeling strength and paper covering strength of Example 2 using a high adhesive masterbatch in the primer-free adhesive layer are significantly improved. In Example 3, by increasing the thickness of the primer-free adhesive layer and reducing the thickness of the functional layer, the friction coefficient of the film is further reduced, the peeling strength and paper covering strength are further improved, and the anti-scratch performance and paper covering strength are further improved.

[0061] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A scratch-resistant primer-free coating film, characterized in that: From top to bottom, it includes a primer-free bonding layer, a core layer, a lower surface layer, and a functional layer; The primer-free adhesive layer comprises the following raw materials in percentage by mass: 4-6% anti-sticking masterbatch and 94-96% linear polyethylene; The core layer comprises the following raw materials in percentage by mass: 99-99.9% homopolypropylene and 0.1-1% antistatic masterbatch; The sub-lower surface layer comprises the following raw materials in percentage by mass: homopolymer polypropylene 99-99.9%, antistatic masterbatch 0.1-0.8%; The functional layer comprises the following raw materials in percentage by mass: 5-8% of spherical synthetic silica and 92-95% of homopolymerized polypropylene.

2. The scratch-resistant primer-free coating film according to claim 1, characterized in that: The antistatic masterbatch comprises homopolypropylene and an antistatic agent, and the melt index of the antistatic agent is 10.0-20.0 g / 10 min.

3. The scratch-resistant primer-free coating film according to claim 2, characterized in that: The antistatic agent comprises glyceryl monostearate, ethoxylated amine and derivatives thereof, and the compounding ratio is 1:0.8 to 1:

2.

4. The scratch-resistant primer-free coating film according to claim 1, characterized in that: The anti-sticking masterbatch comprises 94-96% of linear polyethylene and 4-6% of anti-sticking agent.

5. The scratch-resistant primer-free coating film according to claim 1, characterized in that: The thickness of the functional layer is 0.8-1.2um, the thickness of the sub-lower surface layer is 0.8-1.0um, the thickness of the core layer is 8.9-9.7um, and the thickness of the non-priming adhesive layer is 0.5-0.9um.

6. A method for preparing a scratch-resistant primer-free glossy film, characterized in that: The steps include: The raw materials of the functional layer, the lower surface layer and the non-priming adhesive layer are respectively added to three auxiliary extruders, and the raw materials of the core layer are added to the main extruder, heated and melted, and then composite co-extruded through the die head, cooled by a cold roller to form a cast sheet, and the cast sheet is longitudinally stretched, preheated, transversely stretched, shaped, and cooled to obtain the product.

7. The method for preparing the scratch-resistant primer-free glossy film according to claim 6, characterized in that: The heating and melting temperature of the functional layer and the sub-lower surface layer is 230-245°C, the heating and melting temperature of the core layer is 250-260°C, and the heating and melting temperature of the primer-free adhesive layer is 230-235°C.

8. The method for preparing the scratch-resistant primer-free glossy film according to claim 6, characterized in that: The longitudinal stretching has a stretching ratio of 4.3 to 4.6 and a temperature of 90 to 125°C.

9. The method for preparing the scratch-resistant primer-free glossy film according to claim 6, characterized in that: The temperature of the transverse stretching is 155-170°C.

10. Use of the scratch-resistant glossy film without primer prepared by the preparation method of any one of claims 6 to 9 or the scratch-resistant glossy film without primer according to any one of claims 1 to 5 in paper printing production.

Citation Information

Cited By

  • High-bonding-strength prime-coat-free pre-coating base film for EVA (Ethylene Vinyl Acetate) as well as preparation method and application thereof

    CN120206937A